What would an evidence-based tinnitus patient education program look like? Findings from a scoping review. (2nd July 2020) - Occa, Aurora; Morgan, Susan E.; Scaglione, Tricia Lynn; Kuzbyt, Brianna; Bookman, Richard J.
ABSTRACT: Objective: The purpose of this project was to identify the strategies available to educate patients about tinnitus and to provide guidelines and instructions on how to develop better tinnitus education intervention. Method: A scoping review of peer-reviewed published articles about tinnitus education was conducted. After an initial review of 306 articles, 18 were included in the final review. The information extracted included data on the content conveyed to patients about tinnitus, the format employed, the process used to develop the educational materials, and patients' outcomes linked to tinnitus education. Results: The outcomes provided by the interventions were perceptual, behavioral, and clinical in nature. The format and the content provided by the interventions were heterogeneous. Effective tinnitus education interventions provided specific coping strategies in their curriculum. Conclusion: Educating patients about tinnitus is important to improving their perceptions of the condition and their management behaviors. Healthcare providers and patients need to collaborate to create patient-centered, ad hoc plans. It is important to identify patients' expectations about the outcomes and shared goals. The educational curricula should include basic anatomy and physiology of the auditory system as well as coping strategies, such as attention distraction mechanisms and sound therapy.